ChemInform Abstract: A Magnetically Separable Catalyst for Synthesis of 1‐Phenoxy‐2‐propanol via Atom‐Economic Reaction. Issue 12 (March 2015) - Feng, Shide; Cao, Fengyun; Lu, Bin; Cai, Qinghai
Abstract Reaction of phenol with propylene oxide using a Fe3O4‐supported Al2O3‐MgO catalyst gives the title compound in good yield (80.3% conversion, 88.1% selectivity) via regioselective ring‐opening.